Association and dose–response relationship of plasma magnesium with metabolic syndrome in Chinese adults older than 45 years - Yang, Jingxin; Cao, Yang; Zhang, Huidi; Hu, Yichun; Lu, Jiaxi; Wang, Rui; Feng, Jie; Yang, Lichen (Frontiers in Nutrition, 2024)
Purpose: Magnesium (Mg) is an essential nutrient for the maintenance of vital physiological functions. Magnesium deficiency is associated with type 2 diabetes mellitus (T2DM), and metabolic syndrome (MetS), but conclusions have been inconsistent, and there is a particular lack of evidence regarding this in Chinese populations aged 45 years and older. The aim of this study was to assess the association of plasma Mg with the risk of MetS and its components, and the dose-response relationship in a Chinese population over 45 years of age. Methods: A total of 2101 population were randomly selected from the China Nutrition and Health Surveillance (CNHS) (2015-2017). We used the joint statement of the International Diabetes Federation (IDF) in 2009 to define participants with MetS. The plasma Mg was tested by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The logistic regression and restricted cubic spline (RCS) models were used to analyze the association and dose-response relationship between plasma Mg and MetS and its components. Results: Compared with Q1 for plasma Mg, the ORs and 95% CI for MetS, Impaired fasting glucose (IFG), hypertension, and triglyceride (TG) elevation at the Q5 were 0.419 (0.301,0.583), 0.303 (0.221,0.415), 0.446 (0.322,0.618), and 0.526 (0.384,0.720), respectively, with p-values were all less than 0.05. However, in the components of decreased HDL-C and central obesity, no trend toward lowering with higher plasma magnesium was observed (p=0.717, p=0.865). These associations were not altered by further adjustment for potential confounding variables. RCS analysis showed that when plasma magnesium was lower than 0.85mmol/L, the curve was leveled off, and then the curve showed a decreasing trend with the increase of plasma magnesium. Therefore, plasma Mg was negatively associated with MetS and its components (including IFG, hypertension, and elevated TG) in people older than 45 years. In addition, plasma Mg greater than or equal to 0.85mmol/L, which is higher than the commonly used threshold of 0.75 mmol/L, may be protective against MetS and its components (including elevated FPG, elevated blood pressure, and elevated TG). More prospective studies, such as RCTs, are needed to confirm the effective effect of Mg on MetS and its components.